Intensity modulated radiotherapy in locally advanced thyroid cancer: Outcomes of a sequential phase I dose-escalation study. Issue 1 (April 2018) - Rooney, K.P.; Miah, A.B.; Bhide, S.A.; Guerrero-Urbano, M.T.; Sharabiani, M.T.; Newbold, K.L.; Grove, L.; Harrington, K.J.; Nutting, C.M.
Abstract: Background and purpose: To determine the safety and tolerability of dose-escalation using modestly accelerated IMRT in high-risk locally advanced thyroid cancer requiring post-operative radiotherapy, and to report preliminary data on efficacy. Materials and methods: A sequential Phase I dose-escalation design was used. Dose level one( DL1) received58.8 Gy/2 8F to the post-operative bed and 50 Gy/28F to elective nodes. DL2 received 66.6 Gy/30F to the thyroid bed, 60 Gy/30F to post-operative nodal levels and 54 Gy/30F to elective nodal levels. Acute (NCICTCv.2.0) and late toxicities (RTOG and modified LENTSOM) were recorded. The primary endpoint was the number of patients with ≥Grade 3 (G3) toxicity at 12 months post-treatment. Results: Fifteen patients were recruited to DL1 and twenty-nine to DL2. At 12 months ≥G3 toxicities were 8.3% in both DL1 and DL2. At 60 months, ≥G3 toxicity was reported in 3 (33%) patients in DL1 and 1 (7%) in DL2. One patient in DL2 died at 24 months from radiation-induced toxicity. Time to relapse and overall survival rates were higher in DL2, but this was not statistically significant. Dose-escalation using this accelerated regimen can be safely performed with a toxicity profile similar to reported series using conventional doses.